Pengaruh Penerapan Akuntansi Hijau Dan Kinerja Lingkungan Terhadap Profitabilitas Perusahaan Pertambangan - Airin Nuraini; Thomas Andrew (Institut Bisnis dan Informatika Kesatuan, 2023)
Although natural resources’ important role and massive contribution to the country’s economic development, mining activities bring unprecedent consequences, like environment destruction and social conflict. Companies need to pay attention to the Corporate Social Responsibility (CSR) in this era. Green accounting and environment performance are couple of instruments to support CSR implementation. The puporse of this research is to understand how big the influence of green accounting and environment performance to the mining companies’ profitability. This research is quantitative research. This research utilizes Eviews 13 software. To ensure the precise of model regression, classic assumption test is conducted, such as normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. To choose the best panel data regression model, there will be 3 test to conduct, which are Chow test, Hausman test, and Lagrange-Multiplier test. Partial test and f-test are done to test hypothesis in this research. Partial test and f-test are done to test hypothesis in this research. The result of this research indicates that green accounting gives negative impact to the profitability of mining companies. While, environment performance doesn’t give any influence to the company’s profitability. Simultaneously, green accounting and environment performance give significant influence to the profitability. Green accounting impacts negatively to the profitability, because there is no accounting standard about the calculation method, classification accounts from the environment costs, no correlation between financial report and sustainability report, and lack of transparency of the environment cost. Environment performance gives no effect to the profitability, due to lack respond from some stakeholders to the environment performance score. Keywords : Green Accounting, Environment Performance, Mining Companies